Metabolic syndrome, left ventricular diastolic dysfunction and heart failure with preserved ejective fraction - Zhou, Dan; Lin, Shuisheng; Liu, Zongchen; Yuan, Jiawen; Ren, Huixia; Tan, Huiying; Guo, Yi; Jiang, Xin (Frontiers in Endocrinology, 2025)
Metabolic syndrome (MetS) encompasses a cluster of interrelated conditions, including obesity, hyperglycemia, hyperlipidemia, and hypertension, and has been established as a significant risk factor for cardiovascular events and heightened mortality. At its core, insulin resistance serves as the primary underlying mechanism driving the development of MetS. The prevalence of MetS is rising at an alarming rate, posing a significant public health challenge worldwide. Even in the absence of overt obstructive coronary artery disease or valvular heart disease, patients with MetS often exhibit adverse cardiac remodeling and myocardial dysfunction. Left ventricular hypertrophy (LVH) and left ventricular diastolic dysfunction (LVDD) are the leading manifestations of heart failure with preserved ejection fraction (HFpEF). Abnormal myocardial substrate utilization, neurohormonal activation, interstitial fibrosis, coronary microvascular dysfunction, and metabolic inflammation have all been implicated in the development and progression of adverse cardiac remodeling associated with MetS. However, despite the tremendous research produced on this subject, HFpEF remains highly prevalent in such a population. The early diagnosis of abnormal cardiac remodeling would enable optimal effective therapies to prevent the progression of the disease to the symptomatic phase. HFpEF encompasses a diverse range of pathological processes. In these patients, LVDD and elevated left ventricular filling pressure are the primary manifestations. Echocardiography remains the popular imaging modality for the assessment of LVDD and LV filling pressure. The article aims to review recent articles covering the association between MetS components or MetS and LVDD in HFpEF.